The structure-function relationships of pectins separated from three citrus parts: Flavedo, albedo, and pomace. (March 2023) - Zhang, Lin; Cui, Jiefen; Zhao, Shaojie; Liu, Dan; Zhao, Cheng; Zheng, Jinkai
Abstract: Citrus pectin is the main source of commercial pectin, which is widely used as an emulsifying and gelling agent. However, there is no information on the chemical structure of pectins from different citrus parts, and their functional properties are unclear. In this study, pectins from flavedo, albedo, and pomace were separated by a fractionated processing method, and their chemical structures and emulsifying and gelling properties were investigated to clarify the structure-function relationship. Interestingly, for both pomelo and grapefruit, pectins from different parts showed similar principles; that is, pomace pectin and albedo pectin showed the strongest emulsifying and gelling properties, respectively. Pomace pectin had a high degree of esterification (DE; 86.9%) and medium molecular weight (Mw; 177.7 kDa), and the most compact conformation (i.e., lowest Dmax and Rg values). Thus, it could form a thick layer at the oil-water interface and improve the viscosity of the continuous phase, thereby stabilizing the emulsion. Albedo pectin had the highest DE (89.8%), Mw (258.1 kDa), and proportion of HG region (87.7%); therefore, it gelled rapidly and had the tightest network structure. The findings provide insight into the structure-function relationship of pectin from different citrus parts and will facilitate targeted production of citrus pectin for high-value utilization. Graphical abstract: Image 1 Highlights: Flavedo, albedo, and pomace pectins were separated by a fractionated processing method. The chemical structures of pectins from different citrus parts were carefully compared. The pomace pectins of pomelo and grapefruit had the highest emulsifying properties. The albedo pectins of pomelo and grapefruit showed the strongest gelling properties. The structure-function relationships of pectins from three citrus parts were summarized.